2020
DOI: 10.1177/1178646920956646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotic Administration on Serum Tryptophan Metabolites in Pediatric Type 1 Diabetes Patients

Abstract: Type 1 diabetes (T1D) is characterized by anomalous functioning of the immuno regulatory, tryptophan-catabolic enzyme indoleamine 2,3 dioxygenase 1 (IDO1). In T1D, the levels of kynurenine—the first byproduct of tryptophan degradation via IDO1—are significantly lower than in nondiabetic controls, such that defective immune regulation by IDO1 has been recognized as potentially contributing to autoimmunity in T1D. Because tryptophan catabolism—and the production of immune regulatory catabolites—also occurs via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Pathway analysis using imputed metagenomics based on 16S rRNA sequences revealed tryptophan metabolism as significantly decreased ( q value = 0.045) in group 3 compared with group 1 ( Supplemental Fig. 3 ), which has also been described in T1D patients and mouse model ( 39 ).…”
Section: Resultssupporting
confidence: 55%
“…Pathway analysis using imputed metagenomics based on 16S rRNA sequences revealed tryptophan metabolism as significantly decreased ( q value = 0.045) in group 3 compared with group 1 ( Supplemental Fig. 3 ), which has also been described in T1D patients and mouse model ( 39 ).…”
Section: Resultssupporting
confidence: 55%
“…To what extent the intake of probiotics could increase the production of these compounds with anticancer properties is still uncertain. As mentioned before, probiotics express bile salt hydrolase and increase bile salt metabolism in the gut; an increase in indole-3-propionic acid was observed in rats treated with probiotics [66] but not in children affected with type I diabetes [67]. Increased levels of polyamines have been demonstrated in the elderly after treatment with bifidobacteriacontaining synbiotics [68].…”
Section: Rationale For the Use Of Probiotics In The Treatment Of The ...mentioning
confidence: 70%
“…A prospective cohort study of 7,473 children showed that early probiotic supplementation could reduce the risk of islet autoimmunity in children at the highest genetic risk of T1DM ( 200 ). Another study of 61 young T1DM patients given either Lactobacillus rhamnosus GG or placebo daily for 12 weeks showed that intake of probiotics significantly increased circulating levels of tryptophan and decreased inflammatory cytokine production ( 201 ). The results of a recent randomized, double-blind, and placebo-controlled pilot study assessing treatment with a multispecies probiotic preparation, in 90 children with new-onset T1DM showed that better glycemic control and a decrease in insulin requirements ( 202 ).…”
Section: Gut Microbiome-target Therapiesmentioning
confidence: 99%